ANALISIS YURIDIS TERHADAP WANPRESTASI DALAM PERJANJIAN HUTANG PIUTANG DITINJAU BERDASARKAN HUKUM POSITIF INDONESIA (Studi Putusan Nomor 14/Pdt.g.s/2024/PN.sgr) - Kadek Widya Puspayani; Ni Ketut Sari Adnyani; Komang Febrinayanti Dantes (Jurnal Locus Delicti, 2025)
This study aims to analyze the judge's considerations and legal consequences in cases of breach of debt agreements based on Decision No. 14/Pdt.G.S/2024/PN.Sgr. The focus of the study is the conflict in normative interpretation between Article 1313 of the Civil Code, which allows for unilateral obligations, and Article 1320 of the Civil Code, which requires the agreement of both parties for a valid agreement. This study uses a normative legal approach with qualitative descriptive analysis techniques. The research findings indicate that judges consider a unilateral statement from the defendant as valid evidence of an agreement even though it was not signed by the plaintiff. The study also indicates that judges consider a unilateral statement from the defendant as the valid basis for a legally binding agreement, which is considered to have created legal uncertainty because it does not meet the principle of consensualism required by Article 1320 of the Civil Code. This finding emphasizes the need for harmonization of legal interpretation and clarity of the boundaries between obligations and agreements in the Civil Code. This has implications for legal uncertainty and has the potential to open up loopholes for contradictory legal interpretations in the future.